SURGICAL TREATMENT OF PATIENTS WITH OBSTRUCTION OF PYELOURETERAL SEGMENT - B. K. Komyakov; B. G. Guliev; A. V. Zagazezhev; R. V. Aliev (Вестник хирургии имени И.И. Грекова)
The article presents the operation results of 380 patients (170 (44,7%) men and 210 (55,3%) women) with obstruction of pyeloureteral segment at the period from 1996 to 2014. The middle age was 43,2±7,6 years old. Primary strictures took place in 302 (79,5%) patients and recurrent strictures - in 78 (20,5%). Open and laparoscopic plastic operations were performed in 248 (65,2%), endoscopic surgery - in 112 (29,5%), organo-removal surgery - in 20 (5,3%) cases out of 380 patients with obstruction of pyeloureteral segment. The hines Andersen open pyeloplasty was carried out in 142 (37,4%) patients with primary hydronephrosis out of 152. In addition, an antevasal pyeloureteral anastomosis was formed in 65 (17,1%) cases. Neivert operation was used in 8 (2,1%) cases because of extensive stricture of pyeloureteral segment. Kalp-De Vird pathwise pyeloplasty was fulfilled in 2 (0,5%) patients. Laparoscopic pyeloplasty was performed on 96 (16,7%) patients. These surgeries were carried out by transperitoneal approach using lateral position and 3 or 4 trocars. Endoscopic treatment of pyeloureteral segment was completed in 112 (29,5%) patients. Percutaneous endopyelotomy was used in 42 (11,0%) and retrograde - in 64 (16,8%) cases. Endoplasty of pyeloureteral segment was applied in 6 (1,6%). The efficacy of open pyeloplasty consisted of 93,7% and laparoscopic pyeloplasty - 94,6%. Good results after endopyelotomy were noted in recurrent strictures of pyelouretal segment.